Probing the potential of CdZnTe for high-energy high-flux 2D X-ray detection using the XIDer incremental digital integrating readout - Collonge, Marin; Baussens, Oriane; Busca, Paolo; Fajardo, Pablo; Fischer, Peter; Martin, Thierry; Ritzert, Michael; Ruat, Marie; Schimansky, David; Williams, Morag (Frontiers in Physics, 2024)
The latest synchrotron radiation sources have the capability to produce X-ray beams with a photon flux that can be up to three orders of magnitude higher than previous-generation facilities, and that are not manageable by the currently available 2D photon-counting pixel detectors. The construction of new detectors that exceed the limitations of existing devices is a critical strategic need. Developing such detectors is a challenge in terms of readout electronics as well as sensor material, particularly in the case of devices intended to operate at X-ray energies above 30 keV. The approach adopted at the ESRF to deal with this major difficulty is twofold: the use of a novel semiconductor material with improved electrical properties, high-flux CdZnTe, and the investigation of a specific readout scheme, incremental digital integration, via the XIDer project in collaboration with the University of Heidelberg. Incremental digital integration is a method intended to be less sensitive to variations of the dark current than the conventional charge integration readout. However, this readout scheme requires that the leakage current from the sensor material stays below a certain threshold to reduce the leakage contributions. This paper introduces the ESRF strategy and few examples of the methods employed to evaluate the performance and leakage current behavior of high-flux CdZnTe pixelated sensors. These examples illustrate the first results obtained with this material under moderate to very high X-ray irradiation fluxes of up to 1012 photons/mm2/s.